The military occupational stress response scale: Development, reliability, and validity - Wu, Qianwen; Yang, Zhibing; Qiu, Rui; Cheng, Sizhe; Zhu, Xia; Han, Zheyi; Xiao, Wei (Frontiers in Psychology, 2023)
Soldiers in the military are exposed to numerous stressors, including some that are extreme, and the objective evaluation of soldiers’ occupational stress has become an important topic in current military psychology research. While several tools have been developed to measure stress in this population, none focus specifically on occupational stress. Hence, we developed the Military Occupational Stress Response Scale to provide a tool to objectively measure soldiers’ occupational stress responses. An initial pool of 27 items was assembled from the literature, existing instruments and interviews with soldiers. Of those, 17 were included in the Military Occupational Stress Response Scale. The scale was subsequently completed by soldiers from one military region, and Exploratory Factor Analysis (EFA). and Confirmatory Factor Analyses（CFA） were conducted using Mplus8.3 and IBM SPSS 28.0 softwares. A total of 847 officers and soldiers were selected for scale testing, and 670 subjects were then kept when being cleaned and screened according to the set criteria. After performing the KMO and Bartlett's Test, allowing for a principal component analysis.Through principal components analysis (PCA), we obtained supporting the three-factor model(physiological, psychological and behavioral responses), and which items and factors are strongly correlated，and the confirmatory factor analysis revealed loads of between 0.499 and 0.878 for each item. And the Cronbach α coefficient of the MOSRS is between 0.710 and 0.900, and the Omega reliability is between 0.714 and 0.898, which are all higher than the critical standard of 0.7, indicating that the scale has good reliability，through analysis of discrimination validity of each dimensionand ,We found it has good discrimination validity. The Military Occupational Stress Response Scale (MOSRS) demonstrated sound psychometric characteristics with acceptable reliability and validity, suggesting that it could be used to assess occupational stress in military personnel.